Tradition, Scripture, and Environmental Destruction: Transformation of Ecological Paradigm in Rural Society of Bangka Island - Hidayatullah, Ahmad Syarif (Proceedings of International Conference on Muslim Society and Thought, 2024)
Bangka Island’s artisanal tin mining activity contributes to environmental degradation in the region, affecting certain village areas that have traditionally upheld local wisdom, beliefs, and cultural values. The emergence of an anthropocentric religious perspective, predominantly introduced by educated youth within rural communities, is considered the primary catalyst for a shift in the village community’s paradigm regarding the human-nature relationship. Therefore, this study aims to investigate two aspects: firstly, it delves into the contextual factors that lead to the proliferation of anthropocentric viewpoints among educated youth; and secondly, it examines how such perspectives may diminish the significance of local wisdom and villagers’ beliefs regarding the human-nature connection. Drawing on data gathered through participant observation and ethnographic analysis, the research identifies two main factors contributing to the rise of anthropocentric interpretations of religious texts among educated youth. Firstly, Ulama Nusantara, the Muslim scholars in the archipelago, widely disseminate anthropocentric teachings in their religious references. Secondly, emerging beliefs regard their traditional beliefs in supernatural beings as part of erroneous teachings. By framing Islam, particularly the interpretation of religious texts such as the Quran and Hadith, as a viable solution to societal challenges, young individuals have effectively instigated a shift towards an anthropocentric paradigm. Consequently, this paradigm shift prompts a gradual erosion of traditional values and local wisdom, which have been handed down through generations.